STRATEGI KOMUNIKASI FUNDRAISING ORGANISASI PENGELOLA ZAKAT UNTUK PENINGKATAN PEROLEHAN ZAKAT - Nisrina Cindy Naula; Aan Zainul Anwar (Universitas Darussalam Gontor, 2021)
Zakat is an obligation for every Muslim who fulfills it. Indonesia is a country with a majority Muslim population. The potential for zakat in Indonesia in 2019 is 233.84 trillion, while the reality of the acquisition of new zakat is 3.7 trillion or only 1.3 percent of the potential. It is necessary to explore the problems that arise from these gaps. The purpose of this study is to determine the method of fundraising communication strategy or zakat collection and the results of the implementation of the fundraising strategy or zakat collection by zakat management organizations in Jepara. This research uses descriptive analysis method with a qualitative approach. In extracting data, in-depth interview techniques to the Chairperson and / or the fundraising section, observation of the collection of zakat funds, and documentation through various searches of various libraries and documents of related agencies. Meanwhile, the data processing technique uses the Miles and Huberman theory by carrying out activities such as data reduction, data presentation, and data verification. The results of this study indicate that there are two fundraising communication strategies used by each OPZ, namely, offline and online strategies. The online strategy is considered very effective for NU-CARE LAZISNU Jepara in increasing the acquisition of zakat, while according to BAZNAS Jepara Regency and LAZISMU Jepara, the offline strategy is considered very effective in increasing the acquisition of zakat. Implementation of several strategies that are effectively used by each of these OPZs through the programs implemented